Meningkatkan Keterampilan Membaca Peta Siswa Melalui Permainan Pemilahan Kartu - Chairunnisa, Chairunnisa (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2022)
The purpose of this class action research is to improve the ability to read a map at through the card sorting game. Setting and subjects of this study is the number of 29 students. The procedure of this study was conducted in two cycles, each cycle consisting of planning, action, observation and reflection. Data retrieval test in the form of map reading ability test and non-test the form of observations, interviews, journals students. The achievement of the cycle in dapata the ongoing research process is on Prasiklus I achieve value - average 62.0. In Cycle I achieve value-average 64 and in the second cycle value-average which achieved 75.2. The results showed that after participating in learning to read maps of Tangerang District with a card sorting techniques, the average value obtained by students has increased significantly. Improving the ability of students, followed by behavioral changes from negative to positive.